CITRA PKU MUHAMMADIYAH YOGYAKARTA SEBAGAI RUMAH SAKIT ISLAM - Umarino Umarino; Choirul Fajri; Dani Fadillah (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2017)
The hospitals have an important role in society. A healthy society is one of an indicator of public welfare. PKU Muhammadiyah as one of islamic hospital belonging to Muhammadiyah, have significant roles to realize health in the community. Excellent service is to be done by every hospital, is no exception as PKU islamic hospital. In this research, researchers used research methodology descriptive qualitative. The method selection, intended to see how image PKU as islamic hospital, in the citizens. The data collection method using interviews, and focus group discussion. Results in this research is in the form of articles journals accredited, and proceeding in seminar on national. With the this research, are expected to provide direction/evaluation of policies management PKU in relation to the process of forming image core. Keywords: hospital, image, and islamic.